Computer simulation of stress-strain states in zygomatic bones after complex installation of implants - Timur Dibirov; Aleksey Drobyshev; Eduard Kharazyan; Nikolay Redko; Egor Pankov; Alexander Kozulin; Sergey Panin; Sergey Arutyunov (Fracture and Structural Integrity)
The research addresses evaluation of stress-strain state (SSS) in the zygomatic bonesimplantsdenture base system by varying the type and number of the zygomatic implants, as well as applying loads. The load magnitude was varied over a wide range, characteristic of the mastication process. Changing the adhesion conditions at the zygomatic implantbone tissue interface varied both the level of maximum stress and the location of the critical stress concentrator. The local violation of the integrity of bone tissue in the skull was one of the key reasons for the redistribution of stresses in the zigomatic implant denture base system. Such a phenomenon should be primarily taken into account when choosing the standard sizes of installed zygomatic implants in order to reduce the compliance of weakened areas of the skull (as the basis of the load-bearing structure). Based on the results of the FEM-based computer simulation, the algorithm was proposed for planning prosthetic treatment, which involves the iterative method for selecting both size and location of installing zygomatic implants depending on the results of the SSS calculation and the onset of a critical condition (primarily in bone tissue at the contact area with zygomatic implants).